2004
DOI: 10.1007/978-3-540-28629-5_51
|View full text |Cite
|
Sign up to set email alerts
|

A Protocol for Serializing Unique Strategies

Abstract: Abstract. We devise an efficient protocol by which a series of twoperson games Gi with unique winning strategies can be combined into a single game G with unique winning strategy, even when the result of G is a non-monotone function of the results of the Gi that is unknown to the players. In computational complexity terms, we show that the class UAP of Niedermeier and Rossmanith [NR98] of languages accepted by unambiguous polynomial-time alternating TMs is self-low, i.e., UAP UAP = UAP. It follows that UAP con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The problem of discovering important subgraphs in a large network, however, poses significant computational challenges: the subgraph isomorphism problem, determining whether or not a given graph occurs as a subgraph in a larger graph, is NP-complete [22,115]. On the other hand, graph isomorphism, the special case of subgraph isomorphism when the graphs have the same size, is believed to be an easier problem [96,25], especially given the recent quasi-polynomial time algorithm [2]. A natural algorithm to count k-node motifs is therefore to enumerate subgraphs of size k and test whether they are isomorphic to the given motif.…”
Section: Detecting Network Motifsmentioning
confidence: 99%
“…The problem of discovering important subgraphs in a large network, however, poses significant computational challenges: the subgraph isomorphism problem, determining whether or not a given graph occurs as a subgraph in a larger graph, is NP-complete [22,115]. On the other hand, graph isomorphism, the special case of subgraph isomorphism when the graphs have the same size, is believed to be an easier problem [96,25], especially given the recent quasi-polynomial time algorithm [2]. A natural algorithm to count k-node motifs is therefore to enumerate subgraphs of size k and test whether they are isomorphic to the given motif.…”
Section: Detecting Network Motifsmentioning
confidence: 99%
“…2 Arvind and Kurur [AK02] showed that the graph isomorphism problem (GI) belongs to SPP, a class introduced in [Gup92, OH93,FFK94]. Subsequently, Crasmaru et al [CGRS04] observed that the proof of classifying GI into SPP, as given by Arvind and Kurur [AK02], actually yields a somewhat improved classification for GI: GI belongs to R p s,T (Promise-UP), a subclass of SPP [CGRS04].…”
Section: Definition 210 (Unambiguity Based Hierarchies [Lr94nr98])mentioning
confidence: 99%
“…They introduced the following unambiguity based hierarchies: AUPH, UPH, and U PH. It is known that AUPH ⊆ UPH ⊆ U PH ⊆ UAP [LR94,CGRS04], where UAP (unambiguous alternating polynomial-time) is the analog of UP for alternating polynomialtime Turing machines. These hierarchies received renewed interests in some recent papers (see, for instance, [ACRW04,CGRS04, ST,GT05]).…”
Section: Introductionmentioning
confidence: 99%
“…We prove that the computational complexity of QSCD ff is lower-bounded by that of GA. Well-known upper bounds of GA include NP ∩ co-AM [21,54], SPP [5], and UAP [12]; however, GA is not known to sit in NP ∩ co-NP. Notice that, since most cryptographic problems fall in NP ∩ co-NP, very few cryptographic systems are lower-bounded by the worst-case hardness of problems outside of NP ∩ co-NP.…”
Section: Average-case Hardness Versus Worst-case Hardnessmentioning
confidence: 99%